Engaging Secondary School Learners in a Vocabulary Course through a Spinning Wheel Game - Laila, Maulinasari Nur; Rojabi, Ahmad Ridho; Machfudi, Moch. Imam (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
Vocabulary is essential for students learning English since they can comprehend texts in English more easily once their vocabulary improves. Some teachers in schools continue to use conventional approaches to learning vocabulary, such as distributing textbooks and providing no multimedia resources in the learning environment. These conventional situations bring boredom and a lack of enthusiasm to learners. This study explores the use of spinning wheel media in vocabulary classrooms in one of Jember's private junior high schools. The current study used a qualitative approach, with data gathered through observation, interviews, and document review. The results demonstrated that the spinning wheel media could be used in vocabulary classrooms since it can engage learners, boost their enthusiasm, and improve their vocabulary. Furthermore, the teacher's notes and evaluation showed that this game fosters an engaging and interactive classroom environment.